Refleksi Metafisis Perilaku Bom Bunuh Diri dan Tantangan Bagi Pendidikan Agama Islam - Fahmi, Muhammad; Achmad Muhibin Zuhri; pengelola, pengelola (LPPM STAI Ihyaul Ulum Gresik, 2022)
This article documents the metaphysical reflections in suicide bombing behavior and the challenges for Islamic Religious Education (PAI) in Indonesia. Through library research using content analysis as the analytical method, several findings are produced. It is found that the factors driving suicide bombing behavior in Indonesia include ideological, cultural, socio-economic, geographic, shallow religious understanding, disappointment towards authorities, injustice, and geographical factors. Ideological factors occupy a dominant position when supported by other factors. The metaphysical meaning in suicide bombing behavior can be approached through